High‐Frequency Spinal Cord Stimulation at 10 kHz for the Treatment of Nonsurgical Refractory Back Pain: Design of a Pragmatic, Multicenter, Randomized Controlled Trial. Issue 2 (26th September 2020) - Patel, Naresh; Calodney, Aaron; Kapural, Leonardo; Province‐Azalde, Rose; Lad, Shivanand P.; Pilitsis, Julie; Wu, Chengyuan; Cherry, Taissa; Subbaroyan, Jeyakumar; Gliner, Bradford; Caraway, David
Abstract: Background: Spinal cord stimulation (SCS) has been shown to provide pain relief for chronic back and leg pain due to failed back surgery syndrome. But many patients with chronic back pain have not had major back surgery or are not good candidates for surgery, and conventional medical management (CMM) provides limited relief. We have termed this condition nonsurgical refractory back pain (NSRBP). Level 1 evidence does not yet exist showing the therapeutic benefit of SCS for NSRBP. Objective: To compare 10‐kHz SCS plus CMM (10‐kHz SCS + CMM) to CMM alone for treatment of NSRBP in terms of clinical and cost effectiveness. Study Design: Multicenter, randomized controlled trial (RCT), with subjects randomized 1:1 to either 10‐kHz SCS + CMM or CMM alone. Optional crossover occurs at 6 months if treatment does not achieve ≥50% pain relief. Methods: Patients with NSRBP as defined above may be enrolled if they are ineligible for surgery based on surgical consultation. Subjects randomized to 10‐kHz SCS + CMM will receive a permanent implant if sufficient pain relief is achieved in a temporary trial. Both groups will receive CMM per standard of care and will undergo assessments at baseline and at follow‐ups to 12 months. Self‐report outcomes include pain, disability, sleep, mental health, satisfaction, healthcare utilization, and quality of life. Results: Enrollment was initiated on September 10, 2018. Prespecified independent interim analysis at 40% of the enrollment target indicated the sample size was sufficient to show superiority of treatment at the primary endpoint; therefore, enrollment was stopped at 211. Conclusions: This large multicenter RCT will provide valuable evidence to guide clinical decisions in NSRBP.